Challenges of requirements engineering in the (XP) methodology: a systematic review - Benito Pacheco, Oscar (2023)
The practice of Requirements Engineering (RI) in agile development is substantially different from traditional development. Extreme programming – (XP)(Beck, 2004) is one of the approaches of these agile methods. Traditional methodologies with their waterfall proposal, in pre-established phases, are being replaced by agile methodologies, their interactive and incremental development, with nonstatic requirements. The objective of the study describes an inductive and empirical investigation on challenges and practices with the XP and IR methodology based on an analysis of data collected in academic and scientific literature. To achieve the results, a strategy was implemented that allowed document findings, following the guidelines of a Systematic Literature Review (RSL). In this way, we contribute with a description of challenges in IR in relation to the development of projects with the agile XP methodology.